The impact of movement, physical activity and position on urine production: A pilot study. Issue 11 (28th August 2021) - Deger, Mutlu; Kapila, Vansh; Denys, Marie Astrid; Aridogan, Ibrahim Atilla; Everaert, Karel; Herve, François
Abstract: Background: Many different internal factors have been proven to influence urine production such as age, weight, and quality of sleep. External factors such as consumption of caffeine and fluid consumption have been shown to have an impact on urine production. Aim: To investigate the impact of movement, physical activity and position on urine production. Methods: This prospective observational study was executed at Ghent University Hospital, Belgium. Study participation was open for anyone visiting the hospital. Participants collected one basic and two extended 24‐hour urine collections and filled in questionnaires concerning their general health and physical activity. Urinary levels of osmolality, sodium and creatinine were determined. Data on movement, physical activity and position was described. Results: An increase in body movement leads to a significant increase in diuresis during daytime, night‐time, and 24 hours ( P  = .002, P  < .001, and P  < .001, respectively). An increase in body movement leads to a significant decrease in osmolality during night‐time and 24 hours ( P  = .009, and P  = .004, respectively). However, no significant influence of movement on osmolality was found during daytime ( P  = .12). An increase in body movement leads to a significant decrease in creatinine during daytime, night‐time and 24 hours ( P  = .001, <0.001, and P  < .001, respectively). An increase in body movement leads to a significant increase in sodium during daytime ( P  = .046) but this was statistically significant during night‐time and 24 hours ( P  = .32, and P  = .84 respectively). Conclusion: Our study demonstrates a statistically significant association of movement, physical activity, and position with urine production. It would therefore be interesting to explore this association further with the use of new technology to have more accurate data. Here, lays a potential role for conservative measurements and lifestyle adaptations in the management of patients with bothersome LUTS and more precisely nocturia.